2018
DOI: 10.1590/s0100-204x2018000300007
|View full text |Cite
|
Sign up to set email alerts
|

Morphological characteristics, nutritive quality, and methane production of tropical grasses in Brazil

Abstract: -The objective of this work was to evaluate three tropical forage species for their in vitro methane (CH 4 ) production and organic matter degradability, in order to determine the relationships between forage grass nutritive quality and CH 4 production. Guinea grass (Megathyrsus maximus), palisade grass (Urochloa brizantha), and signal grass (Urochloa decumbens) were evaluated. Palisade grass showed the highest organic matter, neutral detergent fiber, acid detergent fiber, lignin, and lower-crude protein conte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
1
8

Year Published

2018
2018
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 37 publications
(39 reference statements)
1
15
1
8
Order By: Relevance
“…Lower fibre (ADFom, Lignin sa) and higher soluble carbohydrate contents are also desirable characteristics, which, besides improving animal productivity, may also contribute to mitigation of enteric CH 4 emissions in the atmosphere (Beauchemin, Kreuzer, O’Mara, & McAllister, ; Hristov et al, ). Also without significant effect of the increased concentration of atmospheric CO 2 , both treatments showed mean values of CP and TDOM higher and aNDFom, ADFom, Lignin sa, CH 4 production (ml/g MOVD) and PF lower than those observed by Lima et al () evaluating the same grass ( B. brizantha ).…”
Section: Discussioncontrasting
confidence: 53%
“…Lower fibre (ADFom, Lignin sa) and higher soluble carbohydrate contents are also desirable characteristics, which, besides improving animal productivity, may also contribute to mitigation of enteric CH 4 emissions in the atmosphere (Beauchemin, Kreuzer, O’Mara, & McAllister, ; Hristov et al, ). Also without significant effect of the increased concentration of atmospheric CO 2 , both treatments showed mean values of CP and TDOM higher and aNDFom, ADFom, Lignin sa, CH 4 production (ml/g MOVD) and PF lower than those observed by Lima et al () evaluating the same grass ( B. brizantha ).…”
Section: Discussioncontrasting
confidence: 53%
“…However, it requires significant quantities of natural resources and may negatively impact the environment through greenhouse gas (GHG) emissions [1][2][3]. Beef cattle production is pasture-based in tropical regions, but tropical grasses usually have low crude protein (CP), and high neutral detergent fiber (NDF) and acid detergent fiber (ADF) concentrations, which lead to lower animal performance and greater enteric methane (CH 4 ) emissions [2,4].…”
Section: Introductionmentioning
confidence: 99%
“…Echevarria et al (2016) evaluated Urochloa interspecific hybrid BRS RB331 Ipyporã and observed a CP content of 13.8%. Evaluating species of Megathyrsus maximus, Urochloa brizantha and Urochloa decumbens, Lima et al (2018) reported CP contents of 10.2, 4.1 and 10.8% respectively. In a study with acessions of Paspalum atratum Swallen and Paspalum lenticulare Kunth, Marcon et al (2018) observed CP content of 10.1 and 10.8% respectively.…”
Section: Resultsmentioning
confidence: 99%